Expression of HSP70 in cerebral ischemia and neuroprotetive action of hypothermia and ketoprofen Expressão de HSP70 na isquemia cerebral e a ação neuroprotetora da hipotermia e do cetoprofeno - Daniela Pretti da Cunha Tirapelli; Carlos Gilberto Carlotti Junior; João Pereira Leite; Luis Fernando Tirapelli; Benedicto Oscar Colli (Arquivos de Neuro-Psiquiatria)
Heat shock proteins (HSPs) are molecular chaperones that bind to other proteins to shepherd them across membranes and direct them to specific locations within a cell. Several injurious stimuli can induce Hsp70 expression, including ischemia. This study aimed to investigate the pattern of expression of protein (immunohistochemistry) and gene (real-time PCR) Hsp70 in experimental focal cerebral ischemia in rats by occlusion of the middle cerebral artery for 1 hour and the role of neuroprotection with hypothermia (H) and ketoprofen (K). The infarct volume was measured using morphometric analysis defined by triphenyl tetrazolium chloride. It was observed increases in the protein (p=0.0001) and gene (p=0.0001) Hsp70 receptor in the ischemic areas that were reduced by H (protein and gene: p<0.05), K (protein: p<0.001), and H+K (protein: p<0.01 and gene: p<0.05). The Hsp70 increases in the ischemic area suggests that the Hsp70-mediated neuroexcitotoxicity plays an important role in cell death and that the neuroprotective effect of both, H and K are directly involved with the Hsp70. Proteínas de choque térmico (HSPs) são chaperones moleculares que se ligam a outras proteínas para atravessar as membranas e encaminhá-las para locais específicos dentro de uma célula. Vários estímulos nocivos podem induzir a expressão de Hsp70, incluindo isquemia. Este estudo teve como objetivo investigar o padrão de expressão protéica (imunohistoquímica) e gênica (PCR em tempo real) de Hsp70 na isquemia cerebral focal experimental em ratos pela oclusão da artéria cerebral média durante 1 hora e o papel da neuroproteção com hipotermia (H) e cetoprofeno (C). O volume de infarto foi calculado através da análise morfométrica definido por cloreto de trifenil tetrazólio. Foi observado aumento na expressão proteína (p=0,0001) e gênica (p=0,0001) de Hsp70 nas áreas isquêmicas que foram reduzidas pela H (proteína e gene: p<0,05), C (proteína: p<0,001) e H+K (proteína: p<0,01 e gene: p<0,05). O aumento de Hsp70 na área isquêmica sugere que a neuroexcitotoxicidade mediada pela Hsp70 desempenha um papel importante na morte celular e que o efeito neuroprotetor tanto da H quanto do C está diretamente envolvido com a Hsp70.